mRNA quality control goes transcriptional. - Kilchert, C; Vasiljeva, L (2013)
Eukaryotic mRNAs are extensively processed to generate functional transcripts, which are 5' capped, spliced and 3' polyadenylated. Accumulation of unprocessed (aberrant) mRNAs can be deleterious for the cell, hence processing fidelity is closely monitored by QC (quality control) mechanisms that identify erroneous transcripts and initiate their selective removal. Nucleases including Xrn2/Rat1 and the nuclear exosome have been shown to play an important role in the turnover of aberrant mRNAs. Recently, with the growing appreciation that mRNA processing occurs concomitantly with polII (RNA polymerase II) transcription, it has become evident that QC acts at the transcriptional level in addition to degrading aberrant RNAs. In the present review, we discuss mechanisms that allow cells to co-transcriptionally initiate the removal of RNAs as well as down-regulate transcription of transcripts where processing repeatedly fails.